Acute cerebral infarction with adenomyosis in a patient with fever: a case report - Zhao, Yuan (BMC Neurol, 2020)
BACKGROUND: It is reported that acute cerebral infarction with adenomyosis is associated with elevated D-Dimer, elevated CA125, anemia and menstruation. However, previous reports did not notice infection known as fever, which may be a potential risk factor for developing acute cerebral infarction with adenomyosis. CASE PRESENTATION: We describe a 34-year-old woman who presented headache and fever (38 °C) for 4 days and left limb weakness for 1 day during her menstrual phase. Laboratory test data showed: Hemoglobin (HGB) (112 g/L, normal: 120–150 g/L), Carcinoembryonic antigen 125 (CA125) (937.70 U/ml, normal: 0–35 U/ml), D-Dimer (27.4 mg/L, normal: 0–1.5 mg/L). Magnetic resonance imaging (MRI) indicated acute cerebral infarction in right basal ganglia and subcortical region of right frontotemporal lobe. Further, brain computed tomography angiography (CTA) showed that the M1 segment of right middle cerebral artery was strictured and the distal branches of right middle cerebral artery were significantly less than those on the opposite side. No obvious abnormality was found in cranial magnetic resonance venogram (MRV). She had a 5-year history of adenomyosis. No tumors were found by whole body positron emission tomography-computed tomography (PET-CT). We treated this patient by using anti-infective therapy for 1 week and using anticoagulant therapy with low molecular weight heparin for 2 weeks. Subsequently, the anticoagulant therapy was discontinued and replaced by antiplatelet therapy with clopidogrel. We followed up this patient for 4 months, and no recurrence of cerebral infarction was found. CONCLUSIONS: Acute cerebral infarction with adenomyosis may be related to elevated D-Dimer, elevated CA125, anemia and menstruation. Our report suggests that infection may be a potential risk factor for developing acute cerebral infarction with adenomyosis.